The spectrum of charmed mesons from dynamical anisotropic lattices - PEARDON, MICHAEL JAMES; RYAN, SINEAD MARIE (My University, 2007)
We present our preliminary analysis for the chamonium and Ds spectra obtained from Nf = 2 dynamical anisotropic lattices. We use 123?80 lattices with lattice spacing at = 7.35 GeV?1 and anisotropy of six. Meson correlators are computed using all-to-all propagators together with variational analysis.
PUBLISHED
Keywords: Pure & Applied Mathematics